2022
DOI: 10.1021/acs.est.1c06857
|View full text |Cite
|
Sign up to set email alerts
|

Serratia spp. Are Responsible for Nitrogen Fixation Fueled by As(III) Oxidation, a Novel Biogeochemical Process Identified in Mine Tailings

Abstract: Biological nitrogen fixation (BNF) has important environmental implications in tailings by providing bioavailable nitrogen to these habitats and sustaining ecosystem functions. Previously, chemolithotrophic diazotrophs that dominate in mine tailings were shown to use reduced sulfur (S) as the electron donor. Tailings often contain high concentrations of As(III) that might function as an alternative electron donor to fuel BNF. Here, we tested this hypothesis and report on BNF fueled by As(III) oxidation as a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 65 publications
0
28
0
Order By: Relevance
“…Genomic DNA was extracted from tailings with a DNeasy Powersoil kit (QIAGEN, Dresden, Germany) following the manufacturer’s instructions. , The DNA quality and quantity were measured using a NanoDrop ND-2000 spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA) . The 18S rRNA V9 was amplified on the ABI 2720 thermocycler (Applied Biosystems, Carlsbad, CA, USA) using the primer pair 1380F (5′-CCCTGCCHTTTGTACACAC-3′) and 1510R (5′-CCTTCYGCAGGTTCACCTAC-3′) .…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from tailings with a DNeasy Powersoil kit (QIAGEN, Dresden, Germany) following the manufacturer’s instructions. , The DNA quality and quantity were measured using a NanoDrop ND-2000 spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA) . The 18S rRNA V9 was amplified on the ABI 2720 thermocycler (Applied Biosystems, Carlsbad, CA, USA) using the primer pair 1380F (5′-CCCTGCCHTTTGTACACAC-3′) and 1510R (5′-CCTTCYGCAGGTTCACCTAC-3′) .…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria of the genus Serratia are able to effectively remove ammonium from polluted waters by participating in the nitrogen cycle [ 39 ]. In members of the genus Serratia , nitrogen fixation has recently been demonstrated in conjunction with As(III) oxidation, a new process identified in mine tailings [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 50 ]. Among the representatives of this genus, there are known bacteria that fix molecular nitrogen, reduce oxidized nitrogen compounds to ammonium or molecular nitrogen, psychrotolerant phosphate-solubilizing bacteria, as well as reducing oxidized forms of metals, metalloids, and radionuclides [ 40 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microbial diversity is closely related to a variety of ecosystem processes and functions, such as soil nutrient cycling, and is associated with ecosystem stability and health 5 7 . Several studies have found that warming exerts strong effects on microbial diversity; however, results have not been consistent 8 12 .…”
Section: Introductionmentioning
confidence: 99%